Stigma in coronavirus disease-19 survivors in Kashmir, India: A cross-sectional exploratory study - Dar, Shabir Ahmad (PLoS One, 2020)
BACKGROUND: Coronavirus disease-19 (COVID-19) has not only spawned a lot of stigma and discrimination towards its survivors but also to their corpses. We aimed to assess the magnitude and correlates of stigma in these survivors, on return to their communities. METHODS: This was a cross-sectional, hospital-based, exploratory study conducted by the postgraduate department of psychiatry, in collaboration with the postgraduate department of chest medicine, Govt. medical college, Srinagar. The study was performed among COVID-19 survivors, who attended the outpatient department after their discharge from the hospital. Socio-demographic characteristics were recorded through semi-structured proforma. Stigma was measured by the stigma questionnaire. Data was analyzed using descriptive statistics and regression analysis. RESULTS: A total of 91 survivors consented to participate in the study. Almost half (46.2%) of them were in the age group of 30–49 years and close to two-thirds (68.1%) were males. About three–fourths (74.7%) were from the urban background. The mean time from hospital discharge to study entry was 11.7±5.1 [Range(R) = 7–21] days. 98% of survivors provided at least one stigma endorsing response and the total mean stigma score was 28.5±7.1[R = 6–39]. The mean stigma sub-scores were highest for enacted stigma (7.6±1.8) [R = 2–9] and externalized stigma (15.0±4.1) [R = 1–20]. Enacted stigma was significantly high in males as compared to females. Enacted stigma and internalized stigma were both associated with education. Enacted stigma, externalized stigma, disclosure concerns, and total stigma was significantly associated with the occupation. Being unemployed and time since discharge were identified as independent predictors of total stigma. CONCLUSION: Our study results showed high levels of enacted and externalized stigma among COVID-19 survivors. Enacted stigma was more among males and in those who were highly educated. Survivor centered and community-driven anti-stigma programs are the need of the hour to promote the recovery and community re-integration of these survivors.